Plant growth promotion under phosphate deficiency and improved phosphate acquisition by new fungal strain, Penicillium olsonii TLL1 - Suraby, Erinjery Jose; Agisha, Valiya Nadakkakath; Dhandapani, Savitha; Sng, Yee Hwui; Lim, Shi Hui; Naqvi, Naweed I.; Sarojam, Rajani; Yin, Zhongchao; Park, Bong Soo (Frontiers in Microbiology, 2023)
Microbiomes in soil ecosystems play a significant role in solubilizing insoluble inorganic and organic phosphate sources with low availability and mobility in the soil.They transfer the phosphate ion to plants, thereby promoting plant growth. In this study, we isolated an unidentified fungal strain, POT1 (Penicillium olsonii TLL1) from indoor dust samples, and confirmed its ability to promote root growth, especially under phosphate deficiency as well as solubilizing activity for insoluble phosphates such as AlPO4, FePO4•4H2O, Ca3(PO4)2 and hydroxyapatite. Indeed, in vermiculite containing low and insoluble phosphate, the shoot fresh weight of Arabidopsis and leafy vegetable was increased by 2-fold and 3-fold, respectively, with POT1 inoculation. We also conducted tests on crops in Singapore's local soil, which contains highly insoluble phosphate. We confirmed that with POT1, Bok Choy showed a 2-fold increase in shoot fresh weight, and Rice displayed a 2-fold increase in grain yield. Furthermore, we demonstrated that plant growth promotion and phosphate solubilizing activity of POT1 were more effective than those of four different Penicillium strains such as P. bilaiae, P. chrysogenum, P. janthinellum and P. simplicissimum under phosphate limiting conditions. Our findings uncover a new fungal strain and provide a better understanding of symbiotic plant-fungal interactions and suggest the potential use of POT1 as a biofertilizer to improve phosphate uptake and use efficiency in phosphatelimiting conditions.